1992
DOI: 10.1159/000276309
|View full text |Cite
|
Sign up to set email alerts
|

Stapedial Reflex in Parkinson’s Disease

Abstract: In 27 patients with Parkinson’s disease (PD), stapedial reflexes were measured using impedance audiometry and compared with those of 11 age-matched control subjects. The reflex threshold of PD patients was lower than that of control subjects. A prolongation of contraction time (C50) and relaxation time (D50) was revealed. Between patients with and without L-dopa, there was no significant difference for any reflex parameter. But, the D50 of patients without anticholinergic drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Aside from the research by Murofushi et al (1992) on the stapedial reflex in PD, little effort has been made to connect the problems of hypophonia and loudness perception in PD to specific auditory processes. Another strength of this study is that it appears that this is the first study to investigate the effects of background noise in magnitude estimation and magnitude production tasks in a group of individuals with PD.…”
Section: Strengths and Limitations Of The Current Studymentioning
confidence: 99%
“…Aside from the research by Murofushi et al (1992) on the stapedial reflex in PD, little effort has been made to connect the problems of hypophonia and loudness perception in PD to specific auditory processes. Another strength of this study is that it appears that this is the first study to investigate the effects of background noise in magnitude estimation and magnitude production tasks in a group of individuals with PD.…”
Section: Strengths and Limitations Of The Current Studymentioning
confidence: 99%
“…In the present reported study, we found (1) no significant difference between the pure tone audiometric thresholds in the DM1 patients and in the control subjects (at 500 Hz); (2) no significant difference between the SR thresholds in the patients and in the control subjects (500 Hz stimuli); (3) that both C 50 and D 50 in the DM1 patients were significantly prolonged, whereas L was not; (4) and that both C 50 and D 50 in the patients were significantly correlated with (CTG)n length, whereas L was not. Prolonged contraction time (C 50 or corresponding parameters) has been reported in spastic dysphonia [7], multiple sclerosis [4,11,12,18] and Parkinson's disease [20], whereas prolonged relaxation time (D 50 or corresponding measures) has been reported in multiple sclerosis [11], progressive muscular dystrophy [16], sensorineural hearing loss [21], spasmodic dysphonia [19] and Parkinson's disease [20]. Murofushi et al [20] speculated that prolongation of both C 50 and D 50 in Parkinson's disease was caused by hyperactivity of the indirect SR pathway in the brainstem reticular formation.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged contraction time (C 50 or corresponding parameters) has been reported in spastic dysphonia [7], multiple sclerosis [4,11,12,18] and Parkinson's disease [20], whereas prolonged relaxation time (D 50 or corresponding measures) has been reported in multiple sclerosis [11], progressive muscular dystrophy [16], sensorineural hearing loss [21], spasmodic dysphonia [19] and Parkinson's disease [20]. Murofushi et al [20] speculated that prolongation of both C 50 and D 50 in Parkinson's disease was caused by hyperactivity of the indirect SR pathway in the brainstem reticular formation. In DM1 patients, however, it is natural to consider that prolongation of C 50 reflects muscle weakness and that of D 50 myotonia, because there is no evidence of the hyperactivity of the indirect reflex pathways in the brainstems of DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations